Improving social–emotional competence in internationally adopted children with the Attachment and Biobehavioral Catch-up intervention. (August 2021) - Lind, Teresa; Lee Raby, K.; Goldstein, Alison; Bernard, Kristin; Caron, EB; Yarger, Heather A.; Wallin, Allison; Dozier, Mary
Abstract: Children adopted internationally experience adverse conditions prior to adoption, placing them at risk for problematic social–emotional development. The Attachment and Biobehavioral Catch-up (ABC) intervention was designed to help internationally adoptive parents behave in ways that promote young children's social–emotional competence. Participants included 131 parent–child dyads randomly assigned to receive either ABC ( n = 65) or a control intervention ( n = 66). In addition, 48 low-risk biologically related parent–child dyads were included as a comparison group. At follow-up assessments conducted when children were 24 to 36 months old, internationally adopted children who received the ABC intervention had higher levels of parent-reported social–emotional competence than children who received a control intervention. In addition, observational assessments conducted when children were 48 and 60 months of age showed that internationally adopted children who received ABC demonstrated higher social–emotional competence than children who received a control intervention. Adopted children who received the control intervention, but not the ABC intervention, displayed more difficulties with social–emotional competence than low-risk children. Finally, postintervention parent sensitivity mediated the effect of ABC on observed child social–emotional competence in parent interactions, controlling for preintervention parent sensitivity. These results demonstrate the efficacy of a parenting-focused intervention in enhancing social–emotional competence among children adopted internationally.